Methyl 2-amino-4-(3-chloropropoxy)-5-methoxybenzoate - Zhang, Min (International Union of Crystallography, 2009)
The asymmetric unit of the title compound, C(12)H(16)ClNO(4), contains two crystallographically independent molecules. The benzene rings of the two independent molecules are oriented at a dihedral angle of 88.50 (3)°. Intramolecular N—H⋯O hydrogen bonds involving the methoxybenzoate carbonyl group in each molecule result in the formation of two planar, six-membered rings, oriented at dihedral angles of 1.39 (3) and 0.68 (3)° with respect to the adjacent benzene rings. In the crystal structure, intermolecular N—H⋯O hydrogen bonds link the molecules into chains along the a axis.